2017 IEEE Real-Time Systems Symposium (RTSS) 2017
DOI: 10.1109/rtss.2017.00015
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Federated Scheduling of Parallel Real-Time Tasks on Multiprocessors

Abstract: Federated scheduling is a promising approach to schedule parallel real-time tasks on multi-cores, where each heavy task exclusively executes on a number of dedicated processors, while light tasks are treated as sequential sporadic tasks and share the remaining processors. However, federated scheduling suffers resource waste since a heavy task with processing capacity requirement x + (where x is an integer and 0 < < 1) needs x+1 dedicated processors. In the extreme case, almost half of the processing capacity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 38 publications
(60 reference statements)
0
25
0
Order By: Relevance
“…For each of the z semaphores, a DAG is constructed using Algorithm 1. Afterwards, the z resulting DAGs can be scheduled using any approach for multiprocessor DAG scheduling, e.g., global scheduling [29], Federated Scheduling [31] as well as enhanced versions like Semi-Federated Scheduling [25] and Reservation-Based Federated Scheduling [43].…”
Section: Periodic Tasks With Different Periodsmentioning
confidence: 99%
“…For each of the z semaphores, a DAG is constructed using Algorithm 1. Afterwards, the z resulting DAGs can be scheduled using any approach for multiprocessor DAG scheduling, e.g., global scheduling [29], Federated Scheduling [31] as well as enhanced versions like Semi-Federated Scheduling [25] and Reservation-Based Federated Scheduling [43].…”
Section: Periodic Tasks With Different Periodsmentioning
confidence: 99%
“…The scheduling and the schedulability of tasks with precedence constraints on multi-core processors have received recent attention from the real-time community [5][6][7][8][9][10][11][12]. These results consider, mainly, global scheduling.…”
Section: Related Workmentioning
confidence: 99%
“…e1 (5,6) Fig. 1: A task set describing partitioning and precedence constraints between sub-tasks of two DAG tasks τ 1 and τ 2 Each precedence constraint (τ i,j , τ i,k ) ∈ E i imposes that the sub-task τ i,k is not released until τ i,j has completed its execution.…”
Section: Task Model and Notationsmentioning
confidence: 99%
“…Chen [7] later showed that federated scheduling does not admit any constant speedup factor with respect the optimal scheduling algorithm. Jiang et al [12] extended the federated scheduling approach to semi-federated scheduling, in which one or two processors used by a heavy task can be shared with other tasks.…”
Section: Related Workmentioning
confidence: 99%